Cho x/x2-x+1=a . Tính M=x2/x4+x2+1 theo a
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=x+x^2-x^3+x^4-x^5+1+x-x^2+x^3-x^4-x-x^2+x^3-x^4+x^5+1+x-x^2+x^3-x^4\\ =2x-2x^2+2x^3-2x^4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(F\left(x\right)=x^5-3x^2+x^3-x^2-2x+5\)
\(=x^5+x^3-4x^2-2x+5\)
\(G\left(x\right)=x^5-x^4+x^2-3x+x^2+1\)
\(=x^5-x^4+2x^2-3x+1\)
b: Ta có: \(H\left(x\right)=F\left(x\right)+G\left(x\right)\)
\(=x^5+x^3-4x^2-2x+5+x^5-x^4+2x^2-3x+1\)
\(=2x^5-x^4+x^3-2x^2-5x+6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(M\left(x\right)=9x^4+2x^2-x-6\)
\(N\left(x\right)=-x^4-x^3-2x^2+4x+1\)
b: \(P\left(x\right)=8x^4-x^3+3x-5\)
\(Q\left(x\right)=10x^4+x^3+4x^2-5x-7\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(A=x^2+y^2=\left(x+y\right)^2-2xy=15^2-2\cdot50=115\)
c: \(x-y=\sqrt{\left(x+y\right)^2-4xy}=\sqrt{15^2-4\cdot50}=5\)
\(C=x^2-y^2=\left(x+y\right)\left(x-y\right)=15\cdot5=75\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A(x) = x2 + 5x4 - 3x3 + x2 - 4x4 + 3x3 - x + 5
= ( 5x4 - 4x4 ) + ( 3x3 - 3x3 ) + ( x2 + x2 ) - x + 5
= x4 + 2x2 - x + 5
B(x) = x - 5x3 - x2 - x4 + 5x3 - x2 - 3x + 1
= -x4 + ( 5x3 - 5x3 ) + ( -x2 - x2 ) + ( -3x + x ) + 1
= -x4 - 2x2 - 2x + 1
M(x) = A(x) + B(x)
= x4 + 2x2 - x + 5 + ( -x4 - 2x2 - 2x + 1 )
= x4 + 2x2 - x + 5 - x4 - 2x2 - 2x + 1
= -3x + 6
N(x) = A(x) - B(x)
= x4 + 2x2 - x + 5 - ( -x4 - 2x2 - 2x + 1 )
= x4 + 2x2 - x + 5 + x4 + 2x2 + 2x - 1
= 2x4 + 4x2 + x + 4
M(x) = 0 <=> -3x + 6 = 0
<=> -3x = -6
<=> x = 2
Vậy nghiệm của M(x) là 2
![](https://rs.olm.vn/images/avt/0.png?1311)